Phytophagous mites of northeastern Brazil - Moraes, Gilberto J. de; Flechtmann, Carlos H.W. (Pesquisa Agropecuaria Brasileira, 2014)
This paper presents the Tetranychidae (18 species), Tenuipalpidae (two species), Eriophyidae (three species), Rhyncaphytoptidae (one species) and Tarsonemidae (one species) collected in northeastern Brazil. It also presents keys to the genera of Tetranychidae, Tanuipalpidae and Eriophyidae collected, and data on distribution and hosts.